2014
DOI: 10.4054/demres.2014.30.4
|View full text |Cite
|
Sign up to set email alerts
|

Health consequences of child labour in Bangladesh

Abstract: BACKGROUNDThe paper examines the effect of child labour on child health outcomes in Bangladesh, advancing the methodologies and the results of papers published in different journals. OBJECTIVEWe examine the effect of child labour on child health outcomes. METHODSWe used Bangladesh National Child Labour Survey data for 2002-2003 for our analysis. RESULTSThe main finding of the paper suggests that child labour is positively and significantly associated with the probability of being injured or becoming ill. Inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 20 publications
6
35
0
1
Order By: Relevance
“…Furthermore, the frequency of reporting any injury or illness increases with the number of hours worked, with significant variation across employment sectors. 13 A study in Iran reported that industrial workrooms were the most common place for injury (58.2%). Falling from heights or in horizontal surface was the most common mechanism of injury (44%).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the frequency of reporting any injury or illness increases with the number of hours worked, with significant variation across employment sectors. 13 A study in Iran reported that industrial workrooms were the most common place for injury (58.2%). Falling from heights or in horizontal surface was the most common mechanism of injury (44%).…”
Section: Resultsmentioning
confidence: 99%
“…The 1990 United Nations Convention on the Rights of the Child stated that children have a right to basic education and freedom from exploitation (Blunch et al, 2002;Blanchfield, 2013 Child labour has been implicated as the root cause of some problems such as learning disabilities, malnutrition, work-related injuries and mortality (Brooks-Gunn and Duncan, 1997; Ali and Khan, 2012; International Labour Organization, 2013; Ahmed and Ray, 2014). Variants of the problem are endemic in developing countries including Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Variants of the problem are endemic in developing countries including Nigeria. The problem of child labour has become a major issue worldwide as it has become the root cause of avoidable death in children in poor regions of the world (Brooks-Gunn and Duncan, 1997; Ahmed and Ray, 2014;Bashir, 2014). Since the recognition of child labour as a global social and health problem, various efforts have been made towards controlling it however, the literature shows that it remains predominant with sub-Saharan Africa having the highest prevalence rates of child labour with several African nations having over 59% of children working (Abubakar, 2009;UNICEF, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…From these dangers, it is clear that children and youth especially should not be exposed to these environments. However, they continue to be recruited as street vendors because children and youth are able to work long hours for minimal pay (Bhowmik 2005). Participation in child labour is high in the KwaZulu-Natal and Eastern Cape provinces.…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not stop informal labour activities, and research has shown that more than half a million (577,000) children and youth are active participants in the labour market (Statistics SA 2017b). This participation is often for long hours and involves laborious and dangerous work which compromises healthy and safe transition to adulthood (Ahmed and Ray 2014;Hanson, Volonakis, and Al-Rozzi 2015). With children and youth constituting 37 per cent of the total population (Statistics SA 2017b), South Africa should prioritise the safety and educational attainment as this sub-population will likely be the country's future drivers of economic, social and sustainable change.…”
Section: Introductionmentioning
confidence: 99%